Method, device and equipment for evaluating peak regulation balance of power grid and storage medium - LIU YIMING; GU YICAN; ZHANG XINGZI; PANG XUEYUE; LIU HAOYI; XU QIN; MA QIAN; WANG ZIQIANG; QIU GUOBIN; CHEN ZHIGANG; XING HUAN (2023)
The invention discloses a power grid peak regulation balance evaluation method, device and equipment and a storage medium, and the method comprises the steps: obtaining the related data of a power grid in any month, and obtaining a new energy historical actual output coefficient and a new energy predicted output coefficient at a load trough moment through calculation; calculating to obtain a first prediction deviation rate of the new energy power and a second prediction deviation rate of the load; according to the first prediction deviation rate and the second prediction deviation rate, calculating to obtain a system reserve capacity which needs to be reserved by the power grid for dealing with the new energy prediction deviation and the load prediction deviation; and according to the system reserve capacity and the new energy prediction output coefficient at the load valley moment, calculating to obtain unbalanced power of the power grid during the load valley period, and then evaluating the peak regulation